A self-powered nanocellulose suspension concentration sensor and its preparation method and application

By designing a self-powered aramid nanofiber/carbon nanotube composite fiber sensor, the solid-liquid contact electrical response is used to solve the problem of cellulose suspension concentration detection at the nanoscale, achieving accurate and efficient detection and saving energy consumption.

CN116297063BActive Publication Date: 2025-04-25GUANGXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310167317.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-27
Publication Date
2025-04-25
Estimated Expiration
2043-02-27

AI Technical Summary

Technical Problem

The existing fiber suspension concentration detection technology is difficult to achieve accurate and efficient detection of cellulose suspension concentration at the nanoscale, and the structure is complex and requires external energy supply.

Method used

The aramid nanofiber/carbon nanotube composite fiber is combined with the fine copper wire, and the electrical response is initiated through solid-liquid contact, so as to realize the design and preparation of the self-powered nanocellulose suspension concentration sensor.

Benefits of technology

Accurate and efficient detection of nanocellulose suspension concentration is achieved, energy consumption is saved, and the structure is simple and manufacturing costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116297063B_ABST
    Figure CN116297063B_ABST
Patent Text Reader

Abstract

The present invention discloses a self-powered nanocellulose suspension concentration sensor and a preparation method and application thereof, comprising aramid nanofiber / carbon nanotube composite fiber and thin copper wires wound at both ends of the composite fiber, one end of the composite fiber is placed inside a plastic conduit, and the other end is placed outside the plastic conduit, and a sealing structure with a double hole design is adopted at both ends of the plastic conduit, and the thin copper wires and composite fibers exposed on both sides of the plastic conduit are placed outside the sealing structure after penetrating the sealing structure, and the connection parts are sealed with hot melt adhesive, and the thin copper wires exposed on both sides of the plastic conduit are connected to a voltmeter, and the nanocellulose suspension flows into one end of the plastic conduit through the sealing structure and flows out from the other end of the plastic conduit. When the nanocellulose suspension flows through the plastic conduit, a potential difference is generated at both ends of the composite fiber, and an electrical signal is output. The sensor of the present invention can accurately detect the concentration of the nanocellulose suspension and save energy consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sensors, and in particular to a self-powered nanocellulose suspension concentration sensor and a preparation method and application thereof. Background Art

[0002] With the development of materials science and nanotechnology, nanocellulose has become the most attractive renewable natural nanomaterial. Nanocellulose not only has the properties of natural cellulose such as low density, renewable and biodegradable, but also has excellent properties such as large specific surface area, good surface activity, high transparency and good hydrophilicity. It has shown great potential for application in high-performance, functionalized and high value-added products, and has attracted widespread attention. In the process of producing and manufacturing functional products containing nanocellulose, most of the nanocellulose exists in the form of suspension. In order to maintain the stability of production process conditions and ensure product quality, it is necessary to accurately detect the concentration of the nanocellulose suspension. The existing fiber suspension concentration detection technology mainly includes mechanical and optical concentration detection sensors, which are mostly used for the concentration detection of fiber suspensions at the millimeter scale, while there are few reports on the concentration detection sensors of fiber suspensions at the nanoscale. In addition, the existing fiber suspension concentration detection technology also has problems such as complex structure and the need for additional energy for power supply detection. Therefore, it is urgent to obtain new detection methods to achieve accurate and efficient detection of the concentration information of cellulose suspensions at the nanoscale to meet the development and application needs of modern industry.

[0003] In recent years, with the development of sensing technology, material science and emerging energy technology, the application of self-powered sensing technology in the industrial field has received widespread attention. When two materials come into contact and separate due to relative motion, friction charges will be generated at the interface, thereby generating current output. This phenomenon is widely present between solid-solid, solid-liquid and liquid-liquid interfaces where relative motion occurs. Based on this friction electrification effect and the principle of electrostatic induction coupling, the friction nanogenerator realizes the precise detection of physical parameters such as vibration, displacement, pressure, flow rate, etc. This also provides important technical support for the preparation of self-powered nanocellulose suspension concentration sensors and the detection of nanocellulose suspension concentration based on solid-liquid contact electrification response. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a self-powered nanocellulose suspension concentration sensor and a preparation method and application thereof, so as to overcome the deficiencies in the prior art, achieve accurate and efficient detection of the nanocellulose suspension concentration, and save energy consumption.

[0005] In order to achieve the above technical effect, the present invention provides a self-powered nano-cellulose suspension concentration sensor, comprising aramid nanofiber / carbon nanotube composite fibers and thin copper wires wrapped around both ends of the composite fibers, one end of the composite fibers being placed inside a plastic conduit, and the other end being placed outside the plastic conduit, a sealing structure with a double-hole design being adopted at both ends of the plastic conduit, the thin copper wires and the composite fibers exposed on both sides of the plastic conduit are placed outside the sealing structure after passing through the sealing structure, and the connecting parts are sealed with hot-melt adhesive, the thin copper wires exposed on both sides of the plastic conduit are connected to a voltmeter, and the nano-cellulose suspension flows into the plastic conduit from one end through the sealing structure and flows out from the other end of the plastic conduit.

[0006] The present invention also provides a method for preparing a self-powered nanocellulose suspension concentration sensor, comprising the following steps:

[0007] (1) Preparation of aramid nanofiber / carbon nanotube composite fibers: Aramid fibers were dissolved in a dimethyl sulfoxide solution containing deionized water to obtain an aramid nanofiber dispersion, carbon nanotube powder was then added to the aramid nanofiber dispersion, and the mixture was stirred to obtain an aramid nanofiber / carbon nanotube mixed suspension, and the aramid nanofiber / carbon nanotube mixed suspension was injected into an ethanol coagulation bath by a wet spinning method. After immersion for 3 hours, the aramid nanofiber / carbon nanotube composite fibers were extracted from the ethanol coagulation bath and dried at room temperature;

[0008] (2) Wrapping the two ends of the dried aramid nanofiber / carbon nanotube composite fiber with a thin copper wire for several turns to make the composite fiber fully contact with the thin copper wire, and sealing with hot melt adhesive, then inserting the composite fiber into a plastic conduit, with one end of the composite fiber placed inside the plastic conduit and the other end placed outside the plastic conduit. A double-hole sealing structure is used at both ends of the plastic conduit to ensure that the composite fiber is fixed in the center of the plastic conduit, while allowing the nanocellulose suspension to flow into the plastic conduit from one end through the sealing structure and flow out from the other end of the plastic conduit; the thin copper wires exposed on both sides of the plastic conduit and the composite fiber are placed outside the sealing structure after passing through the sealing structure, and the connection parts are sealed with hot melt adhesive. The thin copper wires exposed on both sides of the plastic conduit are connected to a voltmeter. When the nanocellulose suspension flows through the plastic conduit, a potential difference is generated at both ends of the composite fiber, and an electrical signal is output.

[0009] Furthermore, in step (1), the carbon nanotubes are selected from one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, and double-walled carbon nanotubes;

[0010] Furthermore, in step (1), the aramid fiber is selected from para-aramid fiber;

[0011] Furthermore, in step (1), the mass ratio of aramid fiber to carbon nanotube is 4:1 to 1:1;

[0012] Further, the nanocellulose suspension is selected from one or more of a cellulose nanocrystal suspension, a cellulose nanofibril suspension, and a bacterial nanocellulose suspension;

[0013] Furthermore, the mass concentration of the nanocellulose suspension is 0.1% to 0.7%;

[0014] Furthermore, the diameter of the plastic conduit is 10 mm to 100 mm.

[0015] The self-powered nanocellulose suspension concentration sensor of the present invention can be applied to the detection of the concentration of the nanocellulose suspension, thereby achieving accurate and efficient detection of the concentration of the nanocellulose suspension and saving energy consumption.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. The self-powered nanocellulose suspension concentration sensor proposed in the present invention does not require an external power supply system and can convert the flow energy of the nanofiber suspension into electrical energy, thus saving energy;

[0018] 2. The self-powered nanocellulose suspension concentration sensor proposed by the present invention has a simple structure and reduces manufacturing costs;

[0019] 3. The self-powered nanocellulose suspension concentration sensor proposed in the present invention converts the difference in nanocellulose suspension concentration under different flow states into changes in output electrical signals, thereby realizing the detection of concentration information of fiber suspension at the nanoscale and promoting the development of modern nanoscience and technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a schematic diagram of the structure of a sensor according to an embodiment of the present invention;

[0021] Figure 2 It is a schematic diagram of an embodiment of the present invention;

[0022] Figure 3 This is a scanning electron microscope image of the aramid nanofiber / carbon nanotube composite fiber prepared in Example 1;

[0023] Figure 4 The sensor prepared in Example 1 measures the open circuit voltage generated when cellulose nanocrystal (CNC) suspensions of different concentrations flow;

[0024] Figure 5 This is a scanning electron microscope image of the aramid nanofiber / carbon nanotube composite fiber prepared in Example 2;

[0025] Figure 6The sensor prepared in Example 2 measures the open circuit voltage when cellulose nanofibril (CNF) suspensions of different concentrations flow;

[0026] Figure 7 This is a scanning electron microscope image of the aramid nanofiber / carbon nanotube composite fiber prepared in Example 3;

[0027] Figure 8 The sensor prepared in Example 3 measured the open circuit voltage when bacterial nanocellulose (BNC) suspensions of different concentrations flowed;

[0028] Explanation of the reference numerals: 1 - aramid nanofiber / carbon nanotube composite fiber, 2 - thin copper wire, 3 - plastic conduit, 4 - sealing structure, 5 - one end of the plastic conduit, 6 - the other end of the plastic conduit. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be understood that the embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0030] like Figure 1 As shown, the self-powered nanocellulose suspension concentration sensor of the present invention comprises an aramid nanofiber / carbon nanotube composite fiber 1 and a thin copper wire 2 wound around both ends of the composite fiber 1, one end of the composite fiber 1 is placed inside a plastic conduit 3, and the other end is placed outside the plastic conduit 3, a sealing structure 4 with a double hole design is adopted at both ends of the plastic conduit 3, the thin copper wires and the composite fibers exposed on both sides of the plastic conduit 3 are placed outside the sealing structure 4 after penetrating the sealing structure 4, and the connection parts are sealed with hot melt adhesive, the thin copper wires exposed on both sides of the plastic conduit 3 are connected to a voltmeter, and the nanocellulose suspension flows in from one end 5 of the plastic conduit through the sealing structure 4 and flows out from the other end 6 of the plastic conduit.

[0031] Example 1

[0032] In this example, aramid nanofiber / carbon nanotube composite fibers were prepared by a wet spinning process. 3 g of para-aramid fiber was dissolved in 330 g (containing 20 g of deionized water) of dimethyl sulfoxide solution and magnetically stirred at room temperature for 7 days to form a transparent dark red solution, i.e., aramid nanofiber (ANF) suspension. Subsequently, 25% by weight of single-walled carbon nanotube (SWCNTs) powder was added to the ANF suspension, and the ANF / SWCNTs suspension was obtained after mixing evenly. Using a wet spinning method, the mixed ANF / SWCNTs suspension was extruded from a syringe into an ethanol coagulation bath at a constant speed of 1.5 mL / min. The inner diameter of the spinning needle was 3.5 mm. After immersion for 3 h, the composite fiber was extracted from the ethanol coagulation bath and dried at room temperature.

[0033] A 10 cm long aramid nanofiber / carbon nanotube composite fiber was cut, and its two ends were connected to thin copper wires respectively, and then inserted into a polypropylene plastic hose with a diameter of 10 mm, one end of the composite fiber was placed inside the polypropylene plastic hose, and the other end was placed outside the polypropylene plastic hose. A sealing structure with a double hole design was adopted at both ends of the polypropylene plastic hose. The thin copper wires and composite fibers exposed on both sides of the polypropylene plastic hose were placed outside the sealing structure after passing through the sealing structure, and the connecting parts were sealed with hot melt adhesive. The thin copper wires exposed on both sides of the polypropylene plastic hose were connected to a voltmeter, and a cellulose nanocrystal (CNC) suspension with a mass concentration of 0.1-0.4% flowed into one end of the polypropylene plastic hose through the sealing structure and flowed out from the other end of the polypropylene plastic hose.

[0034] like Figure 2 As shown, when the self-powered nanocellulose suspension concentration sensor based on solid-liquid contact electrification response prepared by the method of this embodiment measures the concentration of the flowing nanofiber suspension, in the process of the suspension flowing through the composite fiber surface, the shear stress of the flow field transfers the momentum to the phonons in the carbon nanotubes through the slip layer and excites them, and the generated phonon wind can drive the free electrons in the carbon nanotubes to move. The positive charges in the nanocellulose suspension are first enriched on the composite fiber surface at the inlet end under the attraction of free electrons, gradually covering the fiber surface, and the negative charges in the nanocellulose suspension flow to the outlet end. With the flow of the suspension, the charge distribution at the solid-liquid interface gradually reaches a balanced state, and the free electrons excited by the phonon wind inside the composite fiber are more distributed at the inlet end, thereby generating a potential difference at both ends of the composite fiber, outputting an electrical signal, and realizing the detection of the concentration information of the nanocellulose suspension.

[0035] Figure 3 This is a scanning electron microscope image of the aramid nanofiber / carbon nanotube composite fiber prepared in Example 1. It can be seen from the image that the single-walled carbon nanotube powder particles are evenly distributed on the surface of the composite fiber and form certain protrusions.

[0036] The prepared self-powered nanocellulose suspension concentration sensor was tested using cellulose nanocrystal (CNC) suspension as the fluid, and its electrical signal output performance is shown in Figure 4 .

[0037] Example 2

[0038] In this example, aramid nanofiber / carbon nanotube composite fibers were prepared by a wet spinning process. 3 g of para-aramid fiber was dissolved in 330 g (containing 20 g of deionized water) of dimethyl sulfoxide (DMSO) solution and magnetically stirred at room temperature for 7 days to form a transparent dark red solution, i.e., aramid nanofiber (ANF) suspension. Subsequently, 50% by weight of single-walled carbon nanotube (SWCNTs) powder was added to the ANF suspension, and the ANF / SWCNTs suspension was obtained after mixing evenly. Using a wet spinning method, the mixed ANF / SWCNTs suspension was extruded from a syringe into an ethanol coagulation bath at a constant speed of 1.5 mL / min. The inner diameter of the spinning needle was 3.5 mm. After immersion for 3 h, the composite fiber was extracted from the ethanol coagulation bath and dried at room temperature.

[0039] Cut 8cm long aramid nanofiber / carbon nanotube composite fiber, connect its two ends with thin copper wires respectively, and insert it into a polypropylene plastic hose with a diameter of 15mm. One end of the composite fiber is placed inside the polypropylene plastic hose, and the other end is placed outside the polypropylene plastic hose. The two ends of the polypropylene plastic hose adopt a double-hole design sealing structure. The thin copper wires and composite fibers exposed on both sides of the polypropylene plastic hose are placed outside the sealing structure after passing through the sealing structure, and the connection parts are sealed with hot melt adhesive. The thin copper wires exposed on both sides of the polypropylene plastic hose are connected to a voltmeter. A cellulose nanofibril (CNF) suspension with a mass concentration of 0.1-0.4% flows into one end of the polypropylene plastic hose through the sealing structure and flows out from the other end of the polypropylene plastic hose. The principle of the self-powered nanocellulose suspension concentration sensor prepared by the method of this embodiment when measuring the concentration of the flowing nanocellulose suspension is the same as that of Example 1.

[0040] Figure 5 This is a scanning electron microscope image of the aramid nanofiber / carbon nanotube composite fiber prepared in Example 2. It can be seen from the image that the single-walled carbon nanotube powder particles are evenly distributed on the surface of the composite fiber and form certain protrusions, and the surface roughness is relatively large.

[0041] The prepared self-powered nanocellulose suspension concentration sensor was tested using cellulose nanofibril (CNF) suspension as the fluid, and its electrical signal output performance is shown in Figure 6 .

[0042] Example 3

[0043] In this example, aramid nanofiber / carbon nanotube composite fibers were prepared by a wet spinning process. 3 g of para-aramid fiber was dissolved in 330 g (containing 20 g of deionized water) of dimethyl sulfoxide (DMSO) solution and magnetically stirred at room temperature for 7 days to form a transparent dark red solution, i.e., aramid nanofiber (ANF) suspension. Subsequently, 100% weight specific gravity of single-walled carbon nanotube (SWCNTs) powder was added to the ANF suspension, and the ANF / SWCNTs suspension was obtained after mixing evenly. Using a wet spinning method, the mixed ANF / SWCNTs suspension was extruded from a syringe into an ethanol coagulation bath at a constant speed of 1.5 mL / min. The inner diameter of the spinning needle was 3.5 mm. After immersion for 3 h, the composite fiber was extracted from the ethanol coagulation bath and dried at room temperature.

[0044] Cut a 15cm long aramid nanofiber / carbon nanotube composite fiber, connect its two ends with thin copper wires, and insert it into a polypropylene plastic hose with a diameter of 100mm. One end of the composite fiber is placed inside the polypropylene plastic hose, and the other end is placed outside the polypropylene plastic hose. The two ends of the polypropylene plastic hose adopt a double-hole design sealing structure. The thin copper wires and composite fibers exposed on both sides of the polypropylene plastic hose are placed outside the sealing structure after passing through the sealing structure, and the connection parts are sealed with hot melt adhesive. The thin copper wires exposed on both sides of the polypropylene plastic hose are connected to a voltmeter. The bacterial nanocellulose (BNC) suspension with a mass concentration of 0.5-0.7% flows into one end of the polypropylene plastic hose through the sealing structure and flows out from the other end of the polypropylene plastic hose. The principle of the self-powered nanocellulose suspension concentration sensor prepared by the method of this embodiment when measuring the concentration of the flowing nanocellulose suspension is the same as that of Example 1.

[0045] Figure 7 This is a scanning electron microscope image of the aramid nanofiber / carbon nanotube composite fiber prepared in Example 3. It can be seen from the image that the single-walled carbon nanotube powder particles are evenly distributed on the surface of the composite fiber and form certain protrusions, and the surface roughness is very large.

[0046] The prepared self-powered nanocellulose suspension concentration sensor was tested using bacterial nanocellulose (BNC) suspension as the fluid, and its electrical signal output performance is shown in Figure 8 .

[0047] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the described embodiments. For those skilled in the art, within the scope of the principles and technical ideas of the present invention, various changes, modifications, substitutions and deformations of these embodiments still fall within the protection scope of the present invention.

Claims

1. A self-powered nanocellulose suspension concentration sensor, characterized in that: It includes aramid nanofiber / carbon nanotube composite fibers and thin copper wires wound at both ends of the composite fibers, one end of the composite fibers is placed inside a plastic conduit, and the other end is placed outside the plastic conduit, a sealing structure with a double hole design is used at both ends of the plastic conduit, the thin copper wires and composite fibers exposed at both sides of the plastic conduit are placed outside the sealing structure after penetrating the sealing structure, and the connection parts are sealed with hot melt adhesive, the thin copper wires exposed at both sides of the plastic conduit are connected to a voltmeter, and a nanocellulose suspension flows into the plastic conduit from one end through the sealing structure and flows out from the other end of the plastic conduit; The self-powered nanocellulose suspension concentration sensor is prepared by a method comprising the following steps: (1) Preparation of aramid nanofiber / carbon nanotube composite fibers: Aramid fibers were dissolved in a dimethyl sulfoxide solution containing deionized water to obtain an aramid nanofiber dispersion, carbon nanotube powder was then added to the aramid nanofiber dispersion, and the mixture was stirred to obtain an aramid nanofiber / carbon nanotube mixed suspension, and the aramid nanofiber / carbon nanotube mixed suspension was injected into an ethanol coagulation bath by a wet spinning method. After immersion for 3 hours, the aramid nanofiber / carbon nanotube composite fibers were extracted from the ethanol coagulation bath and dried at room temperature; (2) Wrapping the two ends of the dried aramid nanofiber / carbon nanotube composite fiber with a thin copper wire for several turns to make the composite fiber fully contact with the thin copper wire, and sealing with hot melt adhesive, then inserting the composite fiber into a plastic conduit, with one end of the composite fiber placed inside the plastic conduit and the other end placed outside the plastic conduit. A double-hole sealing structure is used at both ends of the plastic conduit to ensure that the composite fiber is fixed in the center of the plastic conduit, while allowing the nanocellulose suspension to flow into the plastic conduit from one end through the sealing structure and flow out from the other end of the plastic conduit; the thin copper wires exposed on both sides of the plastic conduit and the composite fiber are placed outside the sealing structure after passing through the sealing structure, and the connection parts are sealed with hot melt adhesive. The thin copper wires exposed on both sides of the plastic conduit are connected to a voltmeter. When the nanocellulose suspension flows through the plastic conduit, a potential difference is generated at both ends of the composite fiber, and an electrical signal is output.

2. The self-powered nanocellulose suspension concentration sensor according to claim 1, characterized in that: In the step (1), the carbon nanotubes are selected from one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, and double-walled carbon nanotubes.

3. The self-powered nanocellulose suspension concentration sensor according to claim 1, characterized in that: In the step (1), the aramid fiber is selected from para-aramid fiber.

4. The self-powered nanocellulose suspension concentration sensor according to claim 1, characterized in that: In the step (1), the mass ratio of aramid fiber to carbon nanotube is 4:1 to 1:

1.

5. The self-powered nanocellulose suspension concentration sensor according to claim 1, characterized in that: The nanocellulose suspension is selected from one or more of a cellulose nanocrystal suspension, a cellulose nanofibril suspension, and a bacterial nanocellulose suspension.

6. The self-powered nanocellulose suspension concentration sensor according to claim 1, characterized in that: The mass concentration of the nanocellulose suspension is 0.1% to 0.7%.

7. The self-powered nanocellulose suspension concentration sensor according to claim 1, characterized in that: The diameter of the plastic conduit is 10 mm to 100 mm.

8. Use of the self-powered nanocellulose suspension concentration sensor according to any one of claims 1 to 7 in detecting the concentration of nanocellulose suspension.